IMPLEMENTASI MBKM KEWIRAUSAHAAN: PELATIHAN KONSEP INOVASI USAHA COFFEESHOP JIVALIBRASI DI BINUS - Daffa Afrilliyanto; Koerniawan Hidayat (Jurnal Abdimas Bina Bangsa, 2023)
The increasing growth of MSMEs in coffee shops in the city of Jakarta is a challenge for coffee entrepreneurs. The purpose of this training is to provide knowledge about the importance of innovation for MSME actors, especially beginners, to be able to survive the many coffee shop business competitions. Methods of carrying out activities using online classes, offline classes, online exhibitions, and onsite exhibitions. Creating an innovation concept is divided into several stages: paid advertising, social media marketing, influencer marketing, earned media, and inbound marketing. As a result of this training, participants gain general knowledge and an overview of the world of coffeeshops. They also receive references for making innovations in running a coffeeshop to make it more profitable